ANALISIS TANAH DASAR PONDASI TERHADAP KESTABILAN KEDUDUKAN BANGUNAN - Hartono, Hartono (Politeknik Negeri Semarang, 2012)
A very influential factor in the development of cities in Indonesia are natural population growth and migration from rural to urban areas. The increase in population led to the need for housing is also being increased. The rice fields and hills farm lot converted into residential complexes. Changes in land use is a major cause floods and landslides. The loads addition in body the slopes by making residential building or villa on the edge of a slope or on a hilltop is a effect risky action landslides. From result testing soil housing in Bukit Mutiara Jaya II, the carrying capacity of the land base is still able to support the weight of the building, namely: QB = 0.217 kg / cm2 <Qall = 0.285 kg/cm2 (still safe). On the case of residential Bukit Mutiara Jaya II decreased and the slope of the walls and cracks in some buildings in the residential location, not because of low soil bearing capacity but due to technical error implementation, it is also prone to landslides because the soil in the form of land use in paving pile above the original ground sloped slopes between 15-40%, which is not compacted properly functioned converted into a dwelling or housing. Where land in a pile on the surface of the slope be spread out natural land directly used for the placement of the building foundation besides causing land subsidence and landslides when it rains, it is also due to the spread of the load is not evenly distributed and downs of the carrying capacity of the land caused by decreased physical and mechanical properties due to the presence of water in the soil body slope..